Forecasting of Production and Requirements Broiler Chicken Eggs for Consumption Animal Protein in Aceh Province - Suryana Suryana; Dadang Sukandar (Sarana Ilmu Indonesia (salnesia), 2022)
Nationally, production of broiler eggs chicken continues to increase, however production of broiler eggs chicken in Aceh Province is still low to meet the needs of the people. This study aimed to analyze the forecasting of egg production and demand for broiler chickens in Aceh Province as a source of animal protein contribution. The study was conducted in Aceh Province, which consists of 23 districts/cities. This study used descriptive quantitative methods in narrating a series of time series results obtained from secondary data. A forecasting analysis was carried out on the population, production and egg needs of purebred chickens in Aceh Province for a period of 3 years (2022-2024). There was tendency to decrease from forecasting results (2022, 2023, 2024) on the egg production of purebred chickens in Aceh Province. The egg production of broiler chickens was below the average production value in previous years, which was 8649.0 tons/year. There was a tendency to increase the demand for purebred chicken eggs from 31,008 tons per year to 32,083 tons/year for 2022 to 2024. Based on forecasting results on production and population needs for purebred chicken eggs in Aceh Province, it is not sufficient for the consumption of chicken eggs as a contribution to meet the needs of animal protein.